Efektivitas Program Herregistrasi Dalam Upaya Mewujudkan Pedagang Yang Disiplin Di Pasar Induk Puspa Agro - Reswari, Risma Ardana; Manggalou, Singgih (Jurnal Ilmiah Wahana Pendidikan, 2023)
The her-registration program is a re-registration activity for stall owners at the Puspa Agro Main Market which aims to control traders related to administrative matters and provide traders with an understanding of the importance of security and the facilities that traders get. This program runs with the help of apprentice students as representatives of the marketing team of PT. Puspa Agro. This study aims to determine the effectiveness of the re-registration program in creating disciplined traders. The method used by the author in this research is descriptive research with a qualitative approach. This study uses several variables to measure program effectiveness, namely program socialization, program objectives, and program monitoring. According to the research that has been done, it can be seen that the effectiveness of the re-registration program has not been fully fulfilled. Because in its implementation there are problems such as payment requirements that have not been met by traders and the lack of awareness of traders to re-register which results in traders finding it difficult to re-register. Monitoring and monitoring of the herregistration program has been maximally carried out directly by the Director of PT. Puspa Agro.